Battery Earth: using the subsurface at Boulby underground laboratory to investigate energy storage technologies - Daniels, Katherine A.; Harrington, Jon F.; Wiseall, Andrew C.; Shoemark-Banks, Edward; Hough, Edward; Wallis, Humphrey C.; Paling, Sean M. (Frontiers in Physics, 2023)
Renewable energy provides a low-carbon alternative to power generation in the UK. However, the resultant supply varies on daily, weekly and seasonal cycles, such that for green energies to be fully exploited new grid-scale energy storage systems must be implemented. Two pilot facilities in Germany and the USA have demonstrated the potential of the Earth as a battery to store compressed air, using off-peak surplus energy. Natural accumulations of salt (halite deposits) in the UK represent a large and untapped natural storage reservoir for compressed air with the ability to provide instantaneous green energy to meet peak demand. To realise the potential of this emerging technology, a detailed knowledge of the relationship between mechanics, chemistry and geological properties is required to optimise cavern design, storage potential and economic feasibility. The variable stresses imposed on the rock matrix by gas storage, combined with the cyclic nature of cavern pressurisation are barriers to deployment that need to be addressed to enable large-scale adoption of schemes. Well-designed field experiments are a lynchpin for advancing research in this area, especially when supported by state-of-the-art characterisation and modelling techniques. The research facility at STFC's Boulby Underground Laboratory presents the ideal location to tackle these fundamental issues to optimise 'Battery Earth'.